Unsur Intrinsik Cerpen Kumangmang - Saputra, I Made Dian (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This study aims to describe the intrinsic element of Kumangmang Short Story. The research approach used in this study is descriptive qualitative using structural methods. The data source used is Short Story Kumangmang. The conclusions of this study are: (1) the intrinsic elements found in Kumangmang short stories include themes, background, plot, character, characterization, point of view and mandate. These elements differ from one short story to another.